School Literacy Movement and Strengthening Character Education Against the Formulation of the Core Material of Islamic elementary school - Ahmad Noviansah (eL Bidayah: Journal of Islamic Elementary Education, 2020)
National government policy to make regulations School literacy movement is an effort of the Ministry of Education and Culture in achieving one of its programs, which is to fulfill the nation's children from the age of development to read so that the potential of human resources increases and broadens public involvement in developing and cultivating literacy in Indonesia, the school litersation movement is also a comprehensive and ongoing effort to make schools the first learning organization to be based on, lack of interest in reading or ability literacy has an impact on people's lives. Conceptually, literacy is adopted and promoted by the Ministry of Education and Culture (Kemendikbud), so that character education also arises to develop the character of the nation's children, character education is all that concerns good behavior, character, heart, soul, behavior, perosonality, nature , temperament, character, character, and nature. [Kebijakan pemerintah Nasional untuk membuat peraturan Gerakan literasi sekolah (GLS) adalah suatu upaya Kemeterian Pendidikan dan Kebudayaan dalam mencapai salah programnya yaitu menunbuhkan anak bangsa dari usia perkembangan untuk membaca supaya potensi SDM meningkat dan memperluas keterlibatan publik dalam menumbuh kembangkan dan membudayakan literasi di Indonesia, gerakan litersasi sekolah juga menjadi upaya yang dilakukan secara menyeluh dan berkelanjutan untuk menjadikan sekolah sebagai organisasi pembelajaran pertama dikarnakan, rendahnya minat baca atau kemampuan literasi berdampak dalam kehidupan masyarakat. Secara konseptual pengertian literasi yang diadopsi dan disosialisasikan oleh Kementerian Pendidikan dan Kebudayaan (Kemendikbud), sehingga timbullah juga pendidikan karakter untuk menumbuh kembangkan karakter anak bangsa, pendidikan karakter merupakan semua yang menyangkut perangai baik itu budi pekerti, hati, jiwa, perilaku, perosonalitas, sifat, temperamen, tabiat, watak, dan sifat]